Policy Implications of Seafood Theft By Foreign Parties in Indonesian Waters - Sulistyarini, Dyah Ayu; Setiyono, Joko - (Faculty of Law, Universitas Pekalongan, 2024)
This study aims to examine the effects of foreign parties' policy of stealing marine products in Indonesian waters. The urgency of this research stems from the fact that, as of right now, there is a significant annual increase in the theft of marine products by foreign parties in Indonesian waters. This study uses a normative juridical approach with specifications for descriptive analysis. Secondary data with qualitative data analysis is the type of data used. The study's findings demonstrate that the policy has two (two) positive implications for foreign parties stealing marine products in Indonesian waters. Firstly, the policy's implementation has made the Indonesian government more capable of reducing the theft of marine products and preserving aquatic environments. because it is believed that these actors will employ inappropriate tactics, like the use of explosives, to stop foreign fishermen from taking illegal advantage of marine populations; Second, the ship sinking policy has the negative effect of causing pollution as a result of foreign ships exploding and burning, which can pollute the air near the sea.